The Reality of Quick Commerce Globally: Challenges and Growth Opportunities (Journal of Economic Additions, 2026)
This research aims to analyze the global evolution of quick commerce, highlighting its key challenges, growth opportunities, and strategic success pathways. It considers quick commerce a contemporary business model that gained remarkable momentum in the aftermath of the COVID-19 pandemic.The research findings reveal that quick commerce is no longer merely an extension of e-commerce but has evolved into an independent business model with distinct characteristics. Despite regulatory, behavioral, infrastructural, and logistical constraints, it continues to expand rapidly worldwide. Therefore, developing effective strategic approaches is essential to capitalize on its growth potential and ensure long-term sustainability across diverse international markets
Keywords: Quick Commerce , Reality, Challenges, Growth Opportunities .